Comparative effects of graphene oxide on the interfacial transition zone in silica fume-modified cement mortar at varying water-to-binder ratios - Sumin Im; Seongmin Cho; Junxing Liu; Peiqi Li; Dahyung Jin; Sungwon Sim; Seungmin Lim; Sungchul Bae (Case Studies in Construction Materials)
The interfacial transition zone (ITZ) is the most vulnerable and porous phase in concrete, corresponding to the interface between aggregates and the cement matrix. To densify the ITZ microstructure, this study proposes the incorporation of graphene oxide (GO) into silica fume-modified mortars with high and low water-to-binder (W/B) ratios of 0.4 and 0.2, respectively. GO enhanced the degree of hydration by providing nucleation sites and promoting the pozzolanic reaction of silica fume and Ca(OH)2, leading to the formation of secondary amorphous phases. In the mortars containing GO, the calcium-to-silicon ratio of the phase around the aggregate surface increases because the GO nanosheets absorbed Ca2 + ions and migrated with the mixing water. The comparative effects of GO on the mechanical properties of the ITZ in the mortars with high and low W/B ratios were assessed using nanoindentation tests. The results indicate that the GO nanosheets interlocking with the Ca2+ ions resulted in the formation of denser hydration products with high elastic modulus in the vicinity of the aggregates at a W/B ratio of 0.4 while reducing the amount of unhydrated cement grains at a W/B ratio of 0.2. Overall, this study highlights the comparative effects of GO on enhancing the performance of normal- and high-strength cement composites and mortars, with a particular focus on the improvement of ITZ.